Bone structural changes after gastric bypass surgery evaluated by HR-pQCT: a two-year longitudinal study. Issue 6 (June 2017) - Shanbhogue, Vikram V; Støving, René Klinkby; Frederiksen, Katrine Hartmund; Hanson, Stine; Brixen, Kim; Gram, Jeppe; Jørgensen, Niklas Rye; Hansen, Stinus
Abstract : Objective, design and methods: Roux-en-Y gastric bypass (RYGB) has proved successful in attaining sustained weight loss but may lead to metabolic bone disease. To assess impact on bone mass and structure, we measured a real bone mineral density at the hip and spine by dual-energy X-ray absorptiometry, and volumetric BMD (vBMD) and bone microarchitecture at the distal radius and tibia by high-resolution peripheral quantitative CT in 25 morbidly obese subjects (15 females, 10 males) at 0, 12 and 24 months after RYGB. Bone turnover markers (BTMs), calciotropic and gut hormones and adipokines were measured at the same time points. Results: After a 24.1% mean weight loss from baseline to month 12 ( P < 0.001), body weight plateaued from month 12 to 24 (−0.9%, P = 0.50). However, cortical and trabecular vBMD and microarchitecture deteriorated through the 24 months, such that there was a 5 and 7% reduction in estimated bone strength at the radius and tibia respectively (both P < 0.001). The declines observed in the first 12 months were matched or exceeded by declines in the 12- to 24-month period. While a significant increase in BTMs and decrease in leptin and insulin were seen at 24 months, these changes were maximal at month 12 and stabilized from month 12 to 24. Conclusions: Despite weight stabilization and maintenance of metabolic parameters, bone loss and deterioration in bone strength continued and were substantial in the second year. The clinical importance of these changes in terms of increased risk of developing osteoporosis and fragility fractures remain an important concern.